Comparison of differents methods of sperm selection of llama raw semen - Santa Cruz, R. (2016)
The objective of this study was to compare the efficiency of different sperm selection methods applied to the same llama ejaculate. Four treatments were compared: two variants of the swim up technique (with and without seminal plasma), and two different colloids, Androcoll-E-Large and Percoll®. Using electroejaculation, 21 semen samples were obtained from 7 llama males (n = 7, r = 3). The ejaculates were incubated in a solution of 0.1% collagenase, to decrease thread formation, and then split into 4 aliquots: one aliquot was layered over a column of Androcoll-E-Large (SLC) and the second over a column of Percoll (45%). The third aliquot was deposited in a tube with culture medium and was incubated at a 45° angle for 30 min at 37 °C (SU1). The last aliquot was centrifuged to separate the spermatozoa and seminal plasma. The sperm pellet obtained was resuspended, and transferred to a tube with culture medium which was incubated at an angle of 45° for 30 min at 37 °C (SU2). Both aliquots SLC and P showed higher proportions of progressive motility and plasma membrane functionality (p ≤ 0.05) than raw semen. There were no significant differences (p > 0.05) in sperm viability and in normal spermatozoa between raw semen and treatments. Nevertheless, only SLC did not have a significant increase of bent tails. In conclusion SLC centrifugation would be the method of choice for selecting llama spermatozoa.